Answer:
my answer is in this picture.
Answer:
1. y = 9(x+1/2)^2 -13/4
Step-by-step explanation:
y = 9x^2 + 9x – 1
first isolate the x terms
y = 9(x^2 +x) -1
then add 1/4 inside the brackets to make it a perfect square trinomial (half of the coefficient of the x term squared is how we get 1/4)
since we just added 1/4 we need to subtract what we just added to balance the equation. so 1/4 times 9 is 9/4 ( the number we just added to the equation). then you subtract 9/4 outside of the brackets.
y = 9(x^2 +x +1/4) -1 -9/4
then simplify
y = 9(x+1/2)^2 -13/4
Answer:
Step-by-step explanation:
m = 4 ; (1,-2)
y - y₁ = m (x - x₁)
y - [-2] = 4 (x - 1)
y + 2 = 4x - 4
y = 4x - 4 - 2
y = 4x - 6
Answer: The table and figure are given below,
Solution:
The given equation is
.
put x=0 in the equation.
![2(0)-6y=12](https://tex.z-dn.net/?f=2%280%29-6y%3D12)
![-6y=12](https://tex.z-dn.net/?f=-6y%3D12)
![y=-2](https://tex.z-dn.net/?f=y%3D-2)
Similarly find the values of y at different values of x. The values are shown in the table.
From table it is notices that the value of y=-2 for x=0, y=-1 for x=3, y==-3 for x=-3, y=0 for x=6.
Plot these points in the coordinate plane and joint them by a straight line.
The gra his shown in below figure.
Answer:
Step-by-step explanation?
8 feet 4 inches....12*8= 96, 96+4=100....so your answer is 8 foot 4 inches. because there is 12 inches in a foot, and have 4 left over for the 100.